Internalization of Islamic Educational Values in The Ruwahan Tradition among The Javanese Muslim Community - Shinta Dewi Masitoh; Jaenullah Jaenullah; M. Saidun Anwar (Assyfa Journal of Islamic Studies, 2025)
This study aims to analyze the internalization process of Islamic educational values within the Ruwahan tradition among Javanese Muslim communities and to identify its implications for shaping religious and social character. Using a qualitative approach with an ethnographic design, data were collected through participatory observation, in-depth interviews with religious leaders, community leaders, and youth, as well as documentation. Data analysis employed the interactive model of Miles and Huberman with source and technique triangulation for validity. The findings reveal that the Ruwahan tradition serves as an effective cultural medium for internalizing Islamic educational values through three stages: (1) value transformation, where religious leaders convey faith and moral teachings through tahlil, communal prayers, and religious lectures (tausiyah); (2) value transaction, involving active community participation in mutual cooperation (gotong royong), grave visitation (nyekar), and food charity (berkat), creating a dialogical space for value exchange; and (3) value trans-internalization, where Islamic values become embedded in community personality, manifesting in solidarity, worship discipline, and respect for ancestors. This research contributes to the discourse on cultural-based Islamic education, demonstrating that local traditions can serve as strategic media for character formation amidst modernization challenges. The study recommends strengthening educational aspects of the Ruwahan tradition and increasing youth involvement to ensure its sustainability as a medium for Islamic value internalization